The prevalence of group B streptococcal infection during intrapartum period among high-risk group in labour - Nasr, Bayan; Alalaf, Shahla (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: Pregnancy associated Group B streptococcal infection is a well-established cause of significant neonatal morbidity and mortality. A cross-sectional study was conducted to determine the prevalence of Group B streptococcal infection among women presenting in labor at different ages and gestational ages and its correlation with different risk factors. Methods: Vaginal swab and urine sample for culture from 150 women having risk factors and being in labor and having risk of developing Group B streptococcal infection from 2nd of November 2020 to 2nd of December 2021. Results: The prevalence of Group B streptococcal infection among risky group women during labor in Maternity Teaching Hospital was 8%. The rate of agreement between the vaginal swab results and urine culture results was 92%. There was no significant association between urine culture results with age, parity and prolonged rupture of membrane. A significant high rate of infected urine in culture was found among women with a very extreme preterm gestational age (p value 0.049), and it was also significant among women with pyrexia (p value 0.001). Conclusion: The prevalence of Group B streptococcal infection among high-risk group of women during labor in Maternity Teaching Hospital of Erbil city was 8%.